Cardiac surgery secrets - Soltoski, Paulo R. (Hanley & Belfus, 2000)
Hospital Santa Cruz, Curitiba, Parana, Brazil. Third author, Tomas A. Salerno, is with Univ. of Miami, FL. Contains concise, bulleted lists and questions and answers in a proven format. Also includes the authors' pearls, tips, memory aids, and 'secrets.' For residents and students. Softcover. DNLM: Cardiac Surgical Procedures--Examination Questions.